(untitled) (Nepal Medical College Journal, 2021)
Appendectomy is one of the most common emergency surgical procedures performed in the world. The inflammation of the appendix triggers severe pain in the right lower quadrant of the abdomen. Additionally, the post-operative incision site pain may be distressing to the patients. Analgesic drugs like tramadol (opioid analgesics) and ketorolac (nonsteroidal anti-inflammatory drug - NSAID) are used to manage post-operative pain. The objective was to compare tramadol and ketorolac for pain management by observing the pain-free interval in post-operative patients with appendectomy. A descriptive cross-sectional study was conducted in the department of surgery from November 2019 to May 2020 to observe the duration of pain-free intervals between tramadol and ketorolac. The total number of appendectomy patients selected was 100. Fifty patients received tramadol and the next 50 patients received ketorolac. The data was entered in SPSS and an independent sample t-test was applied to determine the difference in duration of the pain-free interval between ketorolac and tramadol. The average duration of pain-free for the tramadol group was 4.95±1.19 hours (4 hours 57 minutes) while for the ketorolac group was 5.24±1.36 hours (5 hours 14 minutes). The difference was statistically insignificant. We also observed that the tramadol group (88%) received more anti-emetic drugs than the ketorolac group (24%). Therefore, post-operative pain management with ketorolac was found to be as effective as tramadol with comparable duration of the pain free interval.